Mathematical operation and symbol notation
 Statement
L = M ≥ N;
M > P;
L < K.
Conclusions
I. K > P
II. N < K

View Hint View Answer Discuss in Forum
Statement
L = M ≥ N;
M > P;
L < K ;
On combing both the statements, we get
P < L = M ≥ N < k
Conclusions
I. K > P (false)
II. N < K (true)Correct Option: B
Statement
L = M ≥ N;
M > P;
L < K ;
On combing both the statements, we get
P < L = M ≥ N < k
Conclusions
I. K > P (false)
II. N < K (true)
Hence, only Conclusions II is definitely true.
 Statement
U > A = I ≤ 0 < E
Conclusions
I. I ≤ E
II. 0 > U

View Hint View Answer Discuss in Forum
Statement
U > A = I ≤ O < E
Conclusions
I. I ≤ E (false)
II. O > U (false)Correct Option: D
Statement
U > A = I ≤ O < E
Conclusions
I. I ≤ E (false)
II. O > U (false)
Hence, neither Conclusion I nor II is definitely true.
 Statement
A ≤ B < C ;
A ≥ D;
C ≤ F
Conclusions
I. D < C
II. F ≥ D

View Hint View Answer Discuss in Forum
Statement
A ≤ B < C ;
A ≥ D ;
C ≤ F ;
On combining both the statements, we get
D ≤ A ≤ B < C ≤
Conclusions
I. D < C (true)
II. F ≥ D (false)
Hence, only conclusion I is definitely true.Correct Option: A
Statement
A ≤ B < C ;
A ≥ D ;
C ≤ F ;
On combining both the statements, we get
D ≤ A ≤ B < C ≤
Conclusions
I. D < C (true)
II. F ≥ D (false)
Hence, only conclusion I is definitely true.
 Statements
P < Q = R ≥ S ≥ T
Conclusions
I. T ≤ Q
II. R > P

View Hint View Answer Discuss in Forum
Statements
P < Q = R ≥ S ≥ T
Conclusions
I. T ≤ Q
II. R > PCorrect Option: E
Statements
P < Q = R ≥ S ≥ T
Conclusions
I. T ≤ Q (true)
II. R > P (true)
Hence, both conclusions are definitely true.
 Statements
F ≥ G = H;
G > J ≥ K
Conclusions
I. F ≥ K
II. K < H

View Hint View Answer Discuss in Forum
Given that,
D > E ≤ F ............(i)
J < F ......................(ii)
On combining the statements (i) and (ii), we get
D > E ≤ F > J
Conclusions
I. D > J
II. E < JCorrect Option: D
Given that,
D > E ≤ F ............(i)
J < F ......................(ii)
On combining the statements (i) and (ii), we get
D > E ≤ F > J
Conclusions
I. D > J (false)
II. E < J (false)
So, it is clear that neither Conclusion I nor II is true